The spillover effects of political risk, financial risk, and economic freedom on ecological footprint: Empirical evidence from Belt and Road Initiative countries - Junaid Ashraf (Borsa Istanbul Review, 2022)
Determining the relationships between economic freedom, political and financial risk, and ecological footprint has important implications for all nations and surrounding countries' environmental sustainability. Nevertheless, the regional influence of these variables has largely been ignored, particularly in countries that are part of China's Belt and Road Initiative (BRI), with only a few studies examining institutions' participation in reducing environmental degradation. This article expands previous research regarding whether the economic freedom and political and financial risks of surrounding countries can also impact domestic ecological footprints. We apply a spatial dynamic econometric model to a panel of 86 BRI countries from 1995 to 2020 to investigate these influences. Our results demonstrate the presence of regional dependency in countries' ecological footprint, also revealing evident spillover effects of indirect political and financial risks and economic freedom.